Giving Researchers a Headache – Sex and Gender Differences in Migraine - Al-Hassany, Linda; Haas, Jennifer; Piccininni, Marco; Kurth, Tobias; Maassen Van Den Brink, Antoinette; Rohmann, Jessica L. (Frontiers in Neurology, 2020)
Migraine is a common neurovascular disorder affecting approximately 15% of the general population. Ranking second in the list of years lived with disability (YLD), people living with migraine are greatly impacted by this especially burdensome primary headache disorder. In approximately 30% of individuals with migraine, transient neurological symptoms occur (migraine aura) that further increase migraine burden. However, migraine burden is differential with respect to sex. Though one-year prevalences in childhood are similar, from puberty on, the migraine incidence increases at a much higher rate in females than males. Thus, migraine over the life course occurs in women three to four times more often than in men. Attacks are also more severe in women, leading to greater disability and a longer recovery period. The sex disparity in migraine is believed to be partly mediated through fluctuations in ovarian steroid hormones, especially estrogen and progesterone, although the exact mechanisms are not yet completely understood. The release of the neuropeptide calcitonin gene-related peptide (CGRP), followed by activation of the trigeminovascular system, is thought to play a key role in the migraine pathophysiology. Given the burden of migraine and its disproportionate distribution, the underlying cause(s) for the observed differences between sexes in the incidence, frequency, and intensity of migraine attacks must be better understood. Relevant biological, as well as behavioral differences, must be taken into account. To evaluate the scope of the existing knowledge on the issue of biological sex as well as gender differences in migraine, we conducted a systematized review of the currently available research. The review seeks to harmonize existing knowledge on the topic across the domains of biological/preclinical, clinical, and population-level research, which are traditionally synthesized and interpreted in isolation. Ultimately, we identify knowledge gaps and set priorities for further interdisciplinary and informed research on sex and gender differences as well as gender-specific therapies in migraine.